Learning Organization and its Effect on strategic success: Analysis of Private Institutions of Erbil Higher Education - Basne Farooq Jabbar; Ahlam Ibrahim Wali (QALAAI ZANIST JOURNAL, 2021)
To determinate the role of organizational learning across project-based organizations, this study applies a micro-level perspective of organizational learning theory to the social constructivist approach to address relational learning information collaboration that takes into account a strategic perspective involving the development of collective knowledge. The sample was distributed to 180 individuals from different targeted private universities from a total population of 1400 private universities that operate through collaborative ventures to test the research hypotheses. We were able to use 168 surveys in our statistical study after deleting 12 surveys with incorrect responses. Furthermore, value building continues to play a role in bridging the gap between corporate development and long-term strategic growth. Furthermore, exploratory purpose shows a major mediation function in inter-organizational learning, as well as the potential to sustain long-term partnerships with partners, as a beneficial result of partner diversity as a moderate factor. Information convergence was shown to be strongly linked for strategic achievement, as was corporate culture, competences and capabilities, and team cooperation